Role of Endoscopic Third Ventriculostomy in Shunt Malfunction - Sobti, Shivender; Choudhary, Ajay; Bhaskar, Suryanaraynam; Gupta, Laxmi N. (Indian Journal of Neurosurgery, 2017)
Background Shunt placement was a standard treatment for patients with hydrocephalus. The risk of shunt malfunction is quite high. Endoscopic third ventriculostomy (ETV) for hydrocephalus is an important advancement for patients with hydrocephalus. The aim is to study the role of ETV in patients with ventriculoperitoneal shunt malfunction.Methods A prospective study of 21 patients with shunt malfunction, who underwent secondary ETV instead of shunt revision, was conducted in Department of Neurosurgery, PGIMER, and Dr. RML Hospital, New Delhi. Patients data included age, cause of hydrocephalus, number of previous shunt surgeries, and outcome after ETV. Shunt was removed in all patients at the time of ETV. Success was defined as shunt independence till the last follow-up.Results There were 17 males and 4 females. The age range was 2 months to 53 years. Eleven patients had communicating and 10 patients had noncommunicating hydrocephalus. Overall success rate of ETV was 61.90% with 80% (8/10) in noncommunicating and 45.45% (5/11) in communicating hydrocephalus. None of the possible contributing factors for successful ETV, including age (p = 0.088), the etiology of hydrocephalus (p = 0.296), and number of previous shunt surgeries (p = 0.399), were statistically significantly correlated with outcome in our series. Overall complication rate was 14.2%. No death was reported.Conclusion ETV is an effective alternative for patients who present with shunt malfunction. Age, etiology, type of hydrocephalus, and number of shunt revisions did not have a significant impact on outcome of ETV.
Keywords: endoscopic third ventriculostomy; shunt malfunction; hydrocephalus